Bridging Social Capital And Health Outcomes: The Mediating Role Of Maternal Agency In Stunting Prevention Services In Kendari City, Indonesia - Cindy Ayu Oktavia; Rica Tri Septinora; Sri Mulyati (CV. AFDIFAL MAJU BERKAH, 2026)
Degenerative diseases in older adults can cause physical and psychological changes, including anxiety. Spiritual well-being is an important factor that helps older adults accept their illness and undergo treatment more calmly. This study aimed to determine the relationship between spiritual well-being and anxiety levels among older adult patients with degenerative diseases in the inpatient ward of Royal Prima Hospital Jambi. This study used a quantitative approach with a cross-sectional design. The sample consisted of 42 respondents selected through purposive sampling. Data were collected using spiritual well-being and anxiety questionnaires, then analyzed using univariate and bivariate analysis with the Chi-Square test. The results showed that most respondents had moderate spiritual well-being, with 19 respondents (45.2%), and experienced moderate anxiety, with 19 respondents (45.2%). The Chi-Square test obtained a p-value of 0.000 < 0.05, indicating a significant relationship between spiritual well-being and anxiety levels among older adult patients.